PERBANYAKAN IN VITRO TANAMAN BAWANG PUTIH (Allium sativum L.) VARIETAS LUMBU PUTIH MELALUI INDUKSI TUNAS ADVENTIF - Ni Made Armini Wiendi; G. A. Wattimena; Enny Prasetyanti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1996)
Two sets of experiments were conducted to determine the effect of growth hormones, argynine, and coconut water, on the adventitious shoot induction from garlic tissue, and also to find out the best medium for adventitious shoots proliferation. Both experiments could induce direct adventitious shoot and indirect adventitious shoot formation, from calli. Medium with 2 ppm Kinetin and 0.4ppm 2,4-Dproduce good quantity and quality of shoots. The number of shoot from this medium were 32.6 shoots per explant. Medium with 0.5 ppm Kinetin, 0.1 ppm 2.4-D, 25 ppm Argynine, and 10% coconut water produce the highest diameter and good quality of calli, while medium with 1 ppm 2iP and 25 ppm Argynine induced adventitious shoot from calli and produced the highest number of shoot per culture (33.9 shoots).